Electrospun fiber-mediated siRNA delivery and Gene silencing - Long, Hongyan (2016)
While substrate topography influences cell responses, RNA interference (RNAi) has also emerged as a potent method for understanding and directing cell fate. In particular, the three dimensional (3D) electrospun fibers can offer biomimicking topographical signal to alter cell phenotypes, while RNAi can guide cell behaviors through regulating gene expression. Herein, we aim to establish platforms to understand and enhance cellular internalization of small interfering RNA (siRNA) and gene silencing by electrospun nanofiber-mediated RNAi. First, we examined the influence of fiber architecture on siRNA-mediated gene silencing in human somatic cells. The model cell, human dermal fibroblasts (HDFs), were cultured onto aligned and randomly oriented electrospun poly(-caprolactone) (PCL) fibers of different average diameters (300 nm, 700 nm and 1.3 m). It is observed that decreasing fiber diameter from 1.3 m to 300 nm, regardless of fiber orientation, significantly improved housekeeping gene Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and low abundance gene Collagen I silencing efficiencies by ~ 3.8 and ~ 4.4 folds respectively (p<0.05), while the effective siRNA uptake pathway was altered from clathrin-dependent endocytosis to macropinocytosis. Thus, a promising role of fibrous scaffolds in modulating siRNA-mediated gene silencing was illustrated. Second, we furthered our study to establish a RNAi-functionalized nanofibrous platform for translational application by encapsulating siRNA/polymeric micellar complex into electrospun poly(ε-caprolactone)-block-poly(ethyl ethylene phosphate) (PCLEEP) nanofibers. This platform provided cells with the biomimetic environment of natural extracellular matrix, as well as the sustained availability of siRNA for at least 88 days. By using HDFs and mesenchymal stem cells (MSCs) as model somatic and stem cells, we observed that the siRNA/polymeric micellar functionalized PCLEEP fibers significantly enhanced silencing of Collagen I gene expression in HDFs, cyclophilin B gene (CycB) expression in MSCs, and green fluorescent protein (GFP) expression in lentiviral transduced MSCs over-expressing GFP at early time points (Day 3, 7 or 14). Taken together, our results demonstrated that fiber architecture played a significant role in regulating siRNA-mediated gene silencing and we established a novel promising method of delivering siRNA by siRNA/micellar encapsulated nanofibers to efficiently down-regulate gene expression in vitro.